Suicide attempts: epidemiological and clinical characteristics Descriptive study carried out from the EPH of Ouargla 2020-2021 - Soumya Bait (Social Empowerment Journal, 2024)
Suicide attempts are one of the main reasons for hospitalization in medical surgical emergencies. The purpose of our work was to determine the epidemiological and clinical characteristics of patients admitted to medical-surgical emergencies for attempted suicide.We report a descriptive study of 44 cases of attempted suicide admitted to the medico-surgical emergency department of the public hospital Mohamed BOUDIAF Ouargla, during 12 months. The main diagnosis, of the patients included, was a suicide attempt by voluntary intoxication or autolysis.In this study, the female sex was most represented (59%) with sex-ratio = 0, 69. The age group of 16 to 21 was the most represented (32%). The majority of suicides have a low level of instruction (average with a 43 %), 77 % are unemployed and 61 % of singles. The majority of suicidal resided in an urban area, 18% have particular organic affection and 27% have special psycho-psychiatric affection. 45% of suicides have special toxic habits (32% tobacco, 23% psychotropics). 68 % of patients have an exposure to other suicide in the entourage, the ingestion of the caustic was the most used autolysis means at 30 % followed by the '32% drug poisoning. The impulsiveness and the problems of the couple represent the causes of the most found act in 28 % of cases for each. 59% of suicides make TS for the first time and 41% are ≥ 2 times. 64% of suicides have persistent suicidal ideas and that 66% of patients regret their suicidal gesture.The results of our study only reinforce the importance of researching them predictive and precipitating risk factors for suicidal behavior and this, in order to allow prevention, early diagnosis and adaptive management to improve symptomatology, avoid complications and maximally prevent risk from the passage to the self-lytic act.